2022
DOI: 10.36103/ijas.v53i5.1626
|View full text |Cite
|
Sign up to set email alerts
|

Effeciency of Copper Nanoparticles Coated Mint as Anti-Fungal Against Saprolegniasis Disease in Common Carp

Abstract: The present study was aimed to find out the efficacy of M-CuNPs, mint, and CuSO4 in controlling saprolegniasis in common carp. The efficacy of Cu-NP which prepared by using chemical method was examined. 120 fish of weight 80±10g were groups divided into six replications (10 fish/replicate) and the groups were treated as follows: (C-) health without any infection and without treatment, (C+) infected and without treated, (T1 and T2) The fish were infected with the fungus and treated with M-CuNPs at concentration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Also, laboratory treatments with laboratory-purified flavonoids or nanoparticles manufactured from green sources led to an increases in the production of polyphenol oxidase in all fungi used in the experiment. Alwash et al (6), demonstrated in their study that M-CuONPs are selective as an antifungal treatment against Saprolegniasis, where they (M-CuNP) were used as a fair alternative treatment to chemotherapeutic compounds used in aquaculture feeding to achieve a cost-effective, hygienic and environmentally friendly benefit. The reason behind the increases in seeds germinatation could be the stimulating action of nanoparticles in urging to break the dormancy of seeds, which then results in stimulating the cells division of seeds under treatments.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, laboratory treatments with laboratory-purified flavonoids or nanoparticles manufactured from green sources led to an increases in the production of polyphenol oxidase in all fungi used in the experiment. Alwash et al (6), demonstrated in their study that M-CuONPs are selective as an antifungal treatment against Saprolegniasis, where they (M-CuNP) were used as a fair alternative treatment to chemotherapeutic compounds used in aquaculture feeding to achieve a cost-effective, hygienic and environmentally friendly benefit. The reason behind the increases in seeds germinatation could be the stimulating action of nanoparticles in urging to break the dormancy of seeds, which then results in stimulating the cells division of seeds under treatments.…”
Section: Resultsmentioning
confidence: 99%
“…Nano particles approved to have a positive impact as anti-inflammatory and antibacterial effects (8). Copper nanoparticle absorption and accumulation are directly correlated with the concentration used (16) and are easily made in the lab as dark brownish-red powdered items (3,4,6,20). Although the practices of growing Echinacea plants from seeds was common, it has a number of drawbacks, such as the uncertainty that the plants produced will be free of diseases due to their lengthy growth cycles and the dormancy of Echinacea seeds (22,26).…”
Section: Introductionmentioning
confidence: 99%
“…Also, laboratory treatments with laboratory-purified flavonoids or nanoparticles manufactured from green sources led to an increase in the production of polyphenol oxidase in all fungi used in the experiment. Also Alwash et al (3), they demonstrated in their study that M-CuNPs are selective as an antifungal treatment against Saprolegniasis, where they (M-CuNP) were used as a fair alternative treatment to chemotherapeutic compounds used in aquaculture feeding to achieve a cost-effective, hygienic and environmentally friendly benefit. Results in Table 2 and Figure 2 indicate a significant increase in the shoots numbers up to 50mg/ml CuNPs that recording the highest shoots numbers (7.6) then its decreased significantly in 75mg/ml CuNPs (2.4) compared to the value obtained in the concentration of 50mg/ml.…”
Section: Resultsmentioning
confidence: 99%
“…Aquaculture is one of the fastest expanding food-producing industries, with aquaculture setting a world record for production in 2012, accounting for half of all fish destined for human consumption [1], that fish are considered one of the main food sources of proteins, vitamins and minerals, and they are superior to other animal sources in terms of the percentage of protein in its meat [2]. Fish feed constitutes more than 70% of the cost of production in fish projects in general [3], and aquatic feed that contains minerals in the form of nanoparticles may enter cells more easily than their larger counterparts and thus accelerate their absorption in the gastrointestinal tract [4].…”
Section: Introductionmentioning
confidence: 99%